McGraw-Hill's 500 psychology questions : ace your college exams - Ledwith, Kate C. (New York : McGraw-Hill, 2012)
Presents five hundred multiple choice psychology questions similar to those featured on college exams, in addition to detailed explanations of right and wrong answers for each question.
Keywords: Psychology -- Examinations, questions, etc